2020
DOI: 10.1287/mnsc.2019.3459
|View full text |Cite
|
Sign up to set email alerts
|

Prior-Independent Optimal Auctions

Abstract: Auctions are widely used in practice. Although auctions are also extensively studied in the literature, most of the developments rely on the significant common prior assumption. We study the design of optimal prior-independent selling mechanisms: buyers do not have any information about their competitors, and the seller does not know the distribution of values but only knows a general class to which it belongs. Anchored on the canonical model of buyers with independent and identically distributed values, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Dhangwatnotai et al (2010) show that in a single-item two-agent setting when the values are drawn independently and identically from regular distributions, the second-price auction is a 2-approximation in terms of the prior-independent ratio. For this setting, Fu et al (2015) showed that the ratio of 2 is not tight, while Allouah and Besbes (2020) showed that the ratio must lie in the range [1.80, 1.95]. Hartline et al (2020) resolved this question by showing a ratio of 1.91, while also proving that it is tight.…”
Section: Related Workmentioning
confidence: 95%
“…Dhangwatnotai et al (2010) show that in a single-item two-agent setting when the values are drawn independently and identically from regular distributions, the second-price auction is a 2-approximation in terms of the prior-independent ratio. For this setting, Fu et al (2015) showed that the ratio of 2 is not tight, while Allouah and Besbes (2020) showed that the ratio must lie in the range [1.80, 1.95]. Hartline et al (2020) resolved this question by showing a ratio of 1.91, while also proving that it is tight.…”
Section: Related Workmentioning
confidence: 95%
“…Prior-Independent Mechanism Design & Implementation Theory Robust forecast aggregation shares the same spirit as the prior-independent mechanism design (Dhangwatnotai et al, 2010;Devanur et al, 2011;Chawla et al, 2013;Fu et al, 2015;Allouah and Besbes, 2020;Hartline et al, 2020). The problem is formulated as a min-max game between the designer, who designs the aggregator/mechanism, and nature, who picks the prior distribution from a class.…”
Section: Related Workmentioning
confidence: 99%
“…We hope that the insights distilled in this paper will pave the way towards more general separation results with a broader range of applications. This paper also relates to the literature on approximately optimal mechanism design, see, e.g., Dhangwatnotai et al (2015), Hart and Nisan (2017), Allouah and Besbes (2020) and the references therein. Under this modeling paradigm, the seller aims to identify a mechanism for which some objective function (e.g., the expected revenue) is guaranteed to be close to a full information benchmark value (e.g., the maximum expected revenue achievable) under every probability distribution consistent with the assumptions made.…”
Section: Introductionmentioning
confidence: 98%